2021
DOI: 10.4018/ijaci.2021040105
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Step Clustering Approach of Myelinated Nerve Fibers in Experimental Neuromorphology

Abstract: One of the unresolved issues in experimental neuromorphology is searching for a solution for myelinated nerve fibers clustering on set of morphometric parameters. Therefore, in this article, a new approach for cluster analysis of myelinated fibers is proposed based on their morpho-functional features. The proposed clustering approach was developed in R software environment and uses model-based clustering, which is performed in few steps with increasing number of morphometric parameters on each next step. Apply… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Experimental studies play an important role in the determination of morphological alterations or investigation of induced pathological conditions [27]. Thus, Chalouati H et al have found irreversible thyroid changes and hypothyroid state caused by subchronic hexachlorobenzene exposure [28].…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Experimental studies play an important role in the determination of morphological alterations or investigation of induced pathological conditions [27]. Thus, Chalouati H et al have found irreversible thyroid changes and hypothyroid state caused by subchronic hexachlorobenzene exposure [28].…”
Section: Experimental Studiesmentioning
confidence: 99%